2019
DOI: 10.1002/elps.201800540
|View full text |Cite
|
Sign up to set email alerts
|

In situ fabrication of microporous organic network coated capillary column for high resolution gas chromatographic separation of hydrocarbons

Abstract: Microporous organic networks (MONs) are a new class of porous materials synthesized via Sonogashira coupling reactions between organic building blocks. Here we report an in situ synthesis approach to fabricate MONs coated capillary column for high resolution GC separation of hydrocarbons. The McReynolds constant evaluation reveals the MONs coated capillary is a non‐polar column. The MONs coated capillary column shows good resolution for GC separation of diverse important industrial hydrocarbons such as linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In recent years, MONs have exhibited great potential in the fields of gas storage [22,23], contaminant removal [24,25], extraction [26], and sensing [27], owing to their good chemical and thermal stabilities, large surface area, and facile post-functionalization. Such properties, along with their desirable hydrophobicities, render MONs as very promising in separation science, to be used from sample pretreatment to chromatography [28][29][30][31][32][33]. For instance, Jia [32] prepared MOF@MON composites to improve the SPME of aromatics from environmental water, particulate matter (PM 2.5 ), and food samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, MONs have exhibited great potential in the fields of gas storage [22,23], contaminant removal [24,25], extraction [26], and sensing [27], owing to their good chemical and thermal stabilities, large surface area, and facile post-functionalization. Such properties, along with their desirable hydrophobicities, render MONs as very promising in separation science, to be used from sample pretreatment to chromatography [28][29][30][31][32][33]. For instance, Jia [32] prepared MOF@MON composites to improve the SPME of aromatics from environmental water, particulate matter (PM 2.5 ), and food samples.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jia [32] prepared MOF@MON composites to improve the SPME of aromatics from environmental water, particulate matter (PM 2.5 ), and food samples. Our group has reported the fabrication of MON-and chiral-MON-coated capillary columns for GC separation of small alkanes and chiral alcohols [29,30]. Du and Yu et al also reported the fabrication of MON@SiO 2 composites as novel stationary phases for the HPLC separation of diverse aromatics [31,33].…”
Section: Introductionmentioning
confidence: 99%